ANALISIS DAN DESAIN PENERAPAN LOCATION BASEDSERVICE PADA TEMPAT WISATA DAN REKREASI KOTA PALANGKARAYA (Universitas Palangka Raya, 2015)
Palangkaraya travel mobile application is an application that is used to provide information to users about the info tourist locations (in Palangkaraya, Central Kalimantan, Indonesia) along the way. This application is a mobile application technology based Location Based Services (LBS), which is built on the Android platform, using the Eclipse IDE and the Google APIs in its development.In search of the user's position, this application utilizes Global Positioning System (GPS) which has been integrated with the handset. Map and Driving Route is the main facility that is applied with the help of Google Maps API.Database location info in Palangkaraya taken using secondary data where the data is taken from various sources and related agencies. Stored data are tourist sites.